PERAN INOVASI DAN KETERAMPILAN TERHADAP KEBERHASILAN BISNIS CENDERA MATA LOKAL UMKM DI KOTA BANJARBARU - Elma Syifa,; Yusuf Amri Amrullah, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This research is motivated by the importance and how far innovation and skills are to the success of the MSME business. MSMEs that promote cultural preservation cannot be separated from the Innovation and Skills used to become a stage for achieving business success. As has been done by NDFsasirangan's efforts to carry out Innovation and Skills to achieve Business Success. The purpose of this study is to find out how far the role of Innovation and Skills in the success of the NDFsasirangan business is. The research method used is descriptive quantitative research. Data was collected by distributing questionnaires to employees or craftsmen of NDFsasirangan as many as 44 respondents. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that Innovation and Skills play a significant role in business success in the NDFsasirangan business, either partially or simultaneously with the Adjusted R Square (R2)0.62% or the role of innovation and skills by 62% on business success in the NDFsasirangan business.